The pedagogical piano works of Elisenda Fabregas: Teaching repertoire of different styles and contextualizing her work in mainstream repertoire - Baron, Rachel Esther (Kansas State University, 2018)
This lecture-recital presents five pieces from the first two books of Elisenda Fabregas’ Album for the Young. These intermediate-level pieces are written in styles ranging from Renaissance to Modern periods. The goal in presenting these works is to analyze what technical and musical skills they develop, suggest ways to teach these pieces, and to explore their interaction with more traditional teaching repertoire. The lecture-recital presents—pedagogical exercises developed to target specific skills needed to play these pieces; performance practice for each genre represented; and finally, pairs each piece with pieces by Bartok, Bach, Czerny, Kahlua, Clementi, Tchaikovsky, Chopin, and Debussy. The works of Fabregas were chosen to promote the work of women composers and to expand the teaching repertoire that students and teachers are exposed to.
Keywords: Elisenda Fabregas; Intermediate; Mainstream repertoire; Piano pedagogy; Women composers; Contemporary